Therapeutic effect of ascorbic acid on dapsone-induced methemoglobinemia in rats - Kang, Changwoo; Kim, Dong Hoon; Kim, Taeyun; Lee, Soo Hoon; Jeong, Jin Hee; Lee, Sang Bong; Kim, Jin Hyun; Jung, Myeong Hee; Lee, Kyung-woo; Park, In Sung (Clinical and experimental emergency medicine, 2018)
Dapsone (diaminodiphenyl sulfone, DDS) is currently used to treat leprosy, malaria, dermatitis herpetiformis, and other diseases. It is also used to treat pneumocystis pneumonia and Toxoplasma gondii infection in HIV-positive patients. The most common adverse effect of DDS is methemoglobinemia from oxidative stress. Ascorbic acid is an antioxidant and reducing agent that scavenges the free radicals produced by oxidative stress. The present study aimed to investigate the effect of ascorbic acid in the treatment of DDS induced methemoglobinemia. Male Sprague-Dawley rats were divided into three groups: an ascorbic acid group, a methylene blue (MB) group, and a control group. After DDS (40 mg/kg) treatment via oral gavage, ascorbic acid (15 mg/kg), MB (1 mg/kg), or normal saline were administered via tail vein injection. Depending on the duration of the DDS treatment, blood methemoglobin levels, as well as the nitric oxide levels and catalase activity, were measured at 60, 120, or 180 minutes after DDS administration. Methemoglobin concentrations in the ascorbic acid and MB groups were significantly lower compared to those in the control group across multiple time points. The plasma nitric oxide levels and catalase activity were not different among the groups or time points. Intravenous ascorbic acid administration is effective in treating DDS-induced methemoglobinemia in a murine model.